Managing palpitations and arrhythmias during pregnancy - D.L. Adamson; Catherine Nelson‐Piercy (2007)
Arrhythmias in pregnancy are common and may cause concern for the wellbeing of both the mother and the fetus. For some mothers the arrhythmias may be a recurrence of a previously diagnosed arrhythmia or the first presentation in a woman with known structural heart disease. In most cases, however, there is no previous history of heart disease, and the new occurrence of a cardiac problem can generate considerable anxiety. The majority of arrhythmias that occur during pregnancy are benign, and simply troublesome; hence, advice about appropriate actions during symptomatic episodes, together with reassurance, is usually all that is required. In the remaining minority of cases, judicious use of antiarrhythmic drugs will lead to a safe and successful outcome for both mother and baby. While there were no documented maternal deaths from primary arrhythmias in the last UK confidential enquiry into maternal mortality,1 9% of cardiac deaths were defined as sudden adult death syndrome, which raises the possibility of death from a primary arrhythmia. In women with known structural heart disease, however, arrhythmia is one of the five independent predictors of having a cardiac event during the pregnancy and should therefore be treated seriously.2